2001
DOI: 10.1542/peds.107.5.e77
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protease Inhibitor Therapy on Growth and Body Composition in Human Immunodeficiency Virus Type 1-Infected Children

Abstract: ABSTRACT. Objective. To determine the effect of protease inhibitors (PIs) on growth and body composition in children with human immunodeficiency virus type 1 (HIV-1) infection.Background. HIV-1-infected children have chronic problems with both linear growth and weight gain. Viral load may directly influence growth and nutritional status of HIV-1-infected children with reduction of viral load improving the nutritional condition.Design/Methods. Data from 67 patients who initiated PI therapy between 1996 and 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
2
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 28 publications
4
49
2
5
Order By: Relevance
“…However, in a recent study in HIV-1-infected children, protease inhibitors were found to cause a significant increase in weight-for-height and a dramatic improvement in lean body mass over a short interval and had no immediate influence on fat mass, although there was a trend toward increased fat mass, with longer follow-up time. 28 This suggests that in the children whose BMI increased in our study, namely the children with an advance stage of clinical infection and responders to HAART with a high increase in CD4 ϩ T-cell count, lean body mass also increased. The difference of the effect of HAART on body composition between children and adults could be attributed to the fact that children are still growing so their metabolism is different, but additional research is needed.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, in a recent study in HIV-1-infected children, protease inhibitors were found to cause a significant increase in weight-for-height and a dramatic improvement in lean body mass over a short interval and had no immediate influence on fat mass, although there was a trend toward increased fat mass, with longer follow-up time. 28 This suggests that in the children whose BMI increased in our study, namely the children with an advance stage of clinical infection and responders to HAART with a high increase in CD4 ϩ T-cell count, lean body mass also increased. The difference of the effect of HAART on body composition between children and adults could be attributed to the fact that children are still growing so their metabolism is different, but additional research is needed.…”
Section: Discussionmentioning
confidence: 55%
“…28,30,31 However, the follow-up time of these studies was only 24 weeks. A positive influence on growth has been observed as a result of NRTI mono therapy or dual therapy during this same period.…”
Section: Discussionmentioning
confidence: 99%
“…Yet there is evidence that protease inhibitor therapy positively influences nutritional status, including improving body composition. 43 There may have been other factors, such as neurologic deficits, that can influence growth yet were not recorded in the study because it was not designed with growth changes as a primary outcome. However, this study included a large, systematically studied group of HIV-1-infected infants, tracked from birth with close follow-up of important clinical variables.…”
Section: Discussionmentioning
confidence: 99%
“…Such finding is in agreement with a prospective study conducted with children according to which, after the regression model analysis, the therapy with PI improved weight, weight/height, and upper-arm circumference, with significant increased weight since the first assessments. 14 However, a retrospective study found an increase in weight and height after the use of HAART without changes in the BMI. 15 The low height found in the adolescents included in the present study may have been caused by the longer exposure to HIV before the HAART started to be used.…”
Section: Discussionmentioning
confidence: 99%